The effect of intracrystalline chain dynamics on melting and reorganization during heating in semicrystalline polymers. (20th May 2020) - Schulz, Martha; Seidlitz, Anne; Petzold, Albrecht; Thurn-Albrecht, Thomas
Abstract: Using Fast Scanning Calorimetry we investigate the effect of intracrystalline chain dynamics on melting, recrystallization and crystal reorganization during heating, whereby we employ polyethyleneoxide (PEO) and polycaprolactone (PCL) as model polymers with and without such dynamics. We show that in PCL marginally stable crystallites form during isothermal crystallization, which melt immediately upon heating. During further heating continuous melting and recrystallization occurs. At low crystallization temperatures PEO shows a similar behavior, as the intracrystalline dynamics is strongly slowed down. However, during heating the intracrystalline chain dynamics becomes faster leading to fast lamellar thickening and increased thermal stability, until final melting occurs at some high temperature. Our observations demonstrate that melting, recrystallization, and reorganization are competing kinetic processes occurring during heating in semicrystalline polymers. These characteristics cannot be observed by conventional DSC due to low scanning rates and low accessible supercooling. The consequences for the Hoffman–Weeks analysis of polymer melting temperatures are discussed. Highlights: Melting of polymer crystals is affected by intracrystalline chain dynamics. Polymers without or very slow α c -relaxation form marginally stable crystals. Polymers with α c -relaxation reorganize during heating. Melting, recrystallization and reorganization are competing processes.